Maintenance of mouse hematopoietic stem cells ex vivo by reprogramming cellular metabolism - Liu, Xia (Blood, 2015)
The difficulty in maintaining the reconstituting capabilities of hematopoietic stem cells (HSCs) in culture outside of the bone marrow microenvironment has severely limited their utilization for clinical therapy. This hurdle is largely due to the differentiation of long-term stem cells. Emerging evidence suggests that energy metabolism plays an important role in coordinating HSC self-renewal and differentiation. Here, we show that treatment with alexidine dihydrochloride, an antibiotic and a selective inhibitor of the mitochondrial phosphatase Ptpmt1, which is crucial for the differentiation of HSCs, reprogrammed cellular metabolism from mitochondrial aerobic metabolism to glycolysis, resulting in a remarkable preservation of long-term HSCs ex vivo in part through hyperactivation of adenosine 5′-monophosphate–activated protein kinase (AMPK). In addition, inhibition of mitochondrial metabolism and activation of AMPK by metformin, a diabetes drug, also decreased differentiation and helped maintain stem cells in culture. Thus, manipulating metabolic pathways represents an effective new strategy for ex vivo maintenance of HSCs.